Bar Kokhba and leadership as seen through the revolt. Issue 7 (3rd July 2019) - Sheinfeld, Shayna
Abstract: Most of what we know about Bar Kokhba derives from rabbinic and patristic literature, which portrays him as a failed messiah figure. However, the letters and coins found from the revolt itself suggest that Bar Kokhba did not claim to be a messiah figure, but instead was an authoritarian ruler who attempted to control the religious, economic, and military matters of his followers.